Do external diversity practices boost focal firm performance? The case of supplier diversity - Richard, O.; Su, W.; Peng, Mike; Miller, C. (Routledge, 2015)
Based on the resource-based view, we propose that external diversity practices such as supplier diversity may affect firm performance. We find that the relationship between supplier diversity and short-term performance (i.e. productivity) is moderated by context such that firms in declining industries experience positive productivity effects while firms in munificent industries witness negative effects. For longer-term profitability (i.e. Tobin's q), we do not find support for a positive relationship between supplier diversity and long-term performance. However, positive supplier diversity effects emerge in munificent environments. Overall, in support of the strategic human resource management approach, we conclude that the effect of external supplier diversity on firm performance is contingent upon environmental munificence, which documented the necessity to include supplier diversity as a relevant component of a comprehensive diversity and equality management system.